Bidirectional Optogenetic Modulation of the Subthalamic Nucleus in a Rodent Model of Parkinson’s Disease - Xie, Caroline; Power, John; Prasad, Asheeta A. (Frontiers in Neuroscience, 2022)
Parkinson’s disease (PD) is a neurodegenerative disorder characterized by a range of motor symptoms. Treatments are focused on dopamine replacement therapy or deep brain stimulation (DBS). The subthalamic nucleus (STN) is a common target for DBS treatment of PD. However, the function of the STN in normal conditions and pathology is poorly understood. Here, we show in rats that optogenetic modulation of STN neuronal activity exerts bidirectional control of motor function, where inhibition of the STN increases movement and STN activation decreases movement. We also examined the effect of bidirectional optogenetic manipulation STN neuronal activity under dopamine depleted condition using the bilateral rodent 6-hydroxydopamine (6-OHDA) model of Parkinson’s disease. Optogenetic inhibition of the STN in the absence of dopamine had no impact on motor control yet STN excitation led to pronounced abnormal involuntary movement. Administration of levodopa rescued the abnormal involuntary movements induced by STN excitation. Although dopamine and STN dysfunction are well established in PD pathology, here we demonstrate simultaneous STN over activity and loss of dopamine lead to motor deficits. Moreover, we show the dysfunction of the STN is dependent on dopamine. This study provides evidence that the loss of dopamine and the over activity of the STN are key features of PD motor deficits. These results provide insight into the STN pathology in PD and therapeutic mechanism of targeting the STN for the treatment for PD.